(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Lake Alau, a critical water resource in the region, was subject to an extensive water quality assessment with the aim of assessing the impact of human activities on the physico-chemical parameters of Lake Alau, with a specific focus on water quality potentials of the Lake. The study spanned over a year, capturing variations in several physicochemical parameters using standard laboratory techniques. The data were computed and analysed using ANOVA. The findings reveal that the lake generally maintains water quality within permissible limits for aquatic ecosystems. The physical parameters of the lake, including Temperature, Total Solids (TS), Total Dissolved Solids (TDS), and Total Suspended Solids (TSS), were within the range of a productive lake, but higher concentrations of TDS (365.68g/L) and TSS (171.95g/L) might have altered the ecological balance of the lake. The chemical parameters, including pH, biochemical oxygen demand (BOD), Chemical Oxygen Demand (COD), Nitrite, Nitrate, and Phosphate, were within the permissible limit for a productive lake, supporting the biological parameters of the lake However, phosphate concentrations exceed 0.1mg/l which is the limit for drinking water. The observed variations underscore the lake’s vulnerability to human activities and seasonal changes. Despite some concerns, Lake Alau remains suitable for aquatic life, with certain water quality management practices recommended to maintain its intergrity.